Science, magic, and religion : the ritual process of museum magic - Bouquet, Mary, 1955-; Porto, Nuno (New directions in anthropology., 2004)
For some time now, museums have been recognized as important institutions of western cultural and social life. The idea of the museum as a ritual site is fairly new and has been applied to the art museums in Europe and the United States so far. This volume expands it by exploring a range of contemporary museums in Europe and Africa. The case studies examine the different ways in which various actors involved in cultural production dramatize and ritualize such sites. It turns out that not only museum specialists, but visitors themselves are engaged in complex performances and experiences that make use of museums in often unexpected ways.